2021
DOI: 10.1177/2045125321989133
|View full text |Cite
|
Sign up to set email alerts
|

Service-user efforts to maintain their wellbeing during and after successful withdrawal from antipsychotic medication

Abstract: Background: It is well-known that attempting antipsychotic withdrawal can be a fraught process, with a high risk of relapse that often leads people to resume the medication. Nonetheless, there is a group of people who appear to be able to discontinue successfully. Relatively little is known about how people do this. Methods: A convenience sample of adults who had stopped taking antipsychotic medication for more than a year were recruited to participate in semi-structured interviews through an anonymous online … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…Clinicians are often reluctant to reduce or stop antipsychotics due to lack of guidelines, concerns about relapse, and service-level barriers, such as pressure to rapidly discharge and lack of resources to support reduction (Cooper et al, 2019;Moncrieff et al, 2020). With no formal alternative approaches, for some people treatment "choice" can often be reduced to which antipsychotic they want to take and people have reported that they do not feel involved in medication decisions, often feel coerced, and would like to have more choice over their treatment including more support with reducing/stopping these drugs (Larsen-Barr & Seymour, 2021;Morant et al, 2016;Morrison et al, 2012;Read & Sacia, 2020;Roe et al, 2009). As a result, people will often stop antipsychotics abruptly, without clinical support, which may be more likely to lead to adverse outcomes (Horowitz et al, 2021).…”
Section: Treatment For Schizophrenia and Psychosismentioning
confidence: 99%
See 2 more Smart Citations
“…Clinicians are often reluctant to reduce or stop antipsychotics due to lack of guidelines, concerns about relapse, and service-level barriers, such as pressure to rapidly discharge and lack of resources to support reduction (Cooper et al, 2019;Moncrieff et al, 2020). With no formal alternative approaches, for some people treatment "choice" can often be reduced to which antipsychotic they want to take and people have reported that they do not feel involved in medication decisions, often feel coerced, and would like to have more choice over their treatment including more support with reducing/stopping these drugs (Larsen-Barr & Seymour, 2021;Morant et al, 2016;Morrison et al, 2012;Read & Sacia, 2020;Roe et al, 2009). As a result, people will often stop antipsychotics abruptly, without clinical support, which may be more likely to lead to adverse outcomes (Horowitz et al, 2021).…”
Section: Treatment For Schizophrenia and Psychosismentioning
confidence: 99%
“…Although randomised controlled trials show increased rates of relapse following antipsychotic discontinuation over the short-term, not everyone relapses, and relapse does not necessarily indicate a poor long-term outcome. Furthermore, some service users may not prioritise symptom reduction and relapse avoidance to the same extent as services/clinicians (Larsen- Barr & Seymour, 2021). The process of reducing or stopping antipsychotics may itself increase the risk of relapse above that of any concurrent mental health condition due to antipsychotic-withdrawal related effects.…”
Section: Do Antipsychotics Benefit Everyone With a Psychotic Condition?mentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there is a lack of acknowledgement in clinical guidelines on the extent that antipsychotics can induce these effects . Reported antipsychotic withdrawal effects include insomnia, gastrointestinal disturbances, sweating, tremors, dyskinesia, and anxiety (Brandt et al, 2020;Larsen-Barr & Seymour, 2021). No consensus exists over whether withdrawal effects are iatrogenic (Chouinard et al, 2017;Moncrieff, 2006), or whether the experiences are a relapse of a prior diagnosis (Emsley et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Gathering the diversity of experiences of people, who have been through antipsychotic withdrawal, facilitates a better understanding of the potential difficulties. A qualitative study reported frequent experiences of insomnia and anxiety secondary to discontinuation, and symptoms of psychosis and mania (Larsen-Barr & Seymour, 2021). Moreover, 65% of participants in an online survey (n = 650) experienced withdrawal effects (Read & Sacia, 2020).…”
Section: Introductionmentioning
confidence: 99%